Democracy and its elected enemies : American political capture and economic decline - Rosefielde, Steven; Mills, Daniel Quinn (Cambridge : Cambridge University Press, 2013)
Democracy and its Elected Enemies reveals that American politicians have usurped their constitutional authority, substituting their economic and political sovereignty for the people's. This has been accomplished by creating an enormous public service sector operating in the material interest of politicians themselves and of their big business and big social advocacy confederates to the detriment of workers, the middle class and the non-political rich, jeopardizing the nation's security in the process. Steven Rosefielde and Daniel Quinn Mills contend that this usurpation is the source of America's economic decline and fading international power, and provide an action plan for restoring 'true' democracy in which politicians only provide the services people vote for within the civil and property rights protections set forth in the constitution.
Part I: The Challenge of American Politocracy. 1. Hard times; 2. Democracy; 3. Politocracy; 4. Silver lining?; 5. Road to ruin; 6. Burden and spoils; 7. Treadmill of reform -- Part II: How Politocracy Drives American Policy. 8. Subprime mortgage crisis; 9. Foreign imbroglios; 10. Transnationalism -- Part III: Democratic Retreat and Revival. 11. Global retreat; 12. Recovering lost ground.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Democracy -- United States; United States -- Politics and government -- 21st century; United States -- Economic conditions -- 21st century